Women in gambling studies: a poststructural analysis. (4th July 2021) - Palmer du Preez, Katie; Thurlow, Rebecca; Bellringer, Maria
Abstract: Background: Gambling studies literature is a space where discourses call objects such as 'gambling harm reduction' and 'women harmed by gambling' into being and give them status as namable and describable. Methodology and methods: A poststructural feminist analysis of the positioning of women who gamble in gambling studies literature was carried out to explore possibilities and constraints for gambling harm reduction practices. Gambling studies literature was accessed to enable a range of historically emerging framings of women's gambling practices and harm to be brought to light. Discourse analysis drew on key concepts (discourse, subjectivity, power/knowledge) and principles (reversal, discontinuity, specificity and exteriority) developed by Michel Foucault. Findings: Gambling studies have constructed women as: 'risky gamblers', 'vulnerable women', and as subject to gendered socio-cultural determinants of gambling and harm. Dominant conceptualisations of women in gambling studies tend to bring individual women who gamble into focus, obscuring the social, governmental and commercial determinants of gambling and harm, and often reproducing some unhelpful gender stereotypes in the process. Conclusions: Holistic, environmental and Indigenous women's health discourses have the potential to shift gambling harm reduction from a health services approach to one that is focused on supporting community wellbeing. This includes women's co-production and ownership of harm reduction strategies. It is concluded that opportunities women's gambling harm reduction may be found in critical psychology, and/or approaches which emphasize coherent and critical gender analysis, collaborative action, community development and client-led practice.